Behind Successful Refugee Parental Engagement: The Barriers and Challenges - Zaidi, Rahat; Oliver, Christine; Strong, Tom; Alwarraq, Hanan (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
This two-year study examined the barriers and challenges encountered by refugee parents as they negotiate their children’s successful transition into a new school system. The researchers sought to determine what can be learned from parent and educator experiences of these obstacles in order to optimize parent–teacher collaboration for refugee families. Contextualized within a LEAD (Literacy, English and Academic Development) program in an urban centre in Western Canada, the study triangulated data from focus groups comprising Syrian and Iraqi Arabic-speaking families, teachers, and settlement workers. The data were qualitatively analyzed by incorporating Epstein’s six types of parental involvement, a culturally responsive model accounting for parental engagement within the context of home-school-community collaboration (Epstein & Sheldon, 2006). From this model, the researchers make recommendations that include province-wide initiatives to support leadership and teacher training, mandated programming to support refugee and immigrant youth, and the establishment and expansion of board and in-school settlement best practices province-wide.